Pengaruh Keaktifan Mengikuti Kajian Rutin dan Intensitas Melaksanakan Puasa Sunnah Senin-Kamis Terhadap Perilaku Keagamaan Siswa - Dani, Rahmat; Yeli, Salmaini; Hayat, Mardia (Jurnal Inovatif Manajemen Pendidikan Islam, 2024)
This research aims to find the effect of actively participating in routine studies and the intensity of carrying out sunnah fasting Monday and Thursday on the religious behavior of students at the Abdurrab Integrated Islamic Junior High School Pekanbaru. This research is field research with a quantitative approach with research sample was 148 students. The results of this research indicate that active participation in routine studies has a significant influence on the religious behavior of students at the Abdurrab Integrated Islamic Junior High School Pekanbaru. This is shown by the tcount value of 9.500 being greater than ttable 1.976 with an influence of 40.5%. The variable intensity of carrying out sunnah fasting Monday-Thursday has a significant influence on the religious behavior of students at the Abdurrab Pekanbaru Integrated Islamic Junior High School, Pekanbaru. This is shown by the tcount value of 3.060 being greater than ttable 1.976 with an influence of 9.3%. There is a significant influence on the activity of taking part in routine studies and the intensity of carrying out sunnah fasting simultaneously Monday-Thursday on the religious behavior of students at the Abdurrab Integrated Islamic Junior High School Pekanbaru.